Naître vers la fin : circularités dans Alumbramiento de Víctor Erice - Miguel Rodrigo (Cahiers de Civilisation Espagnole Contemporaine)
In a filmography where the narrative is often greatly weakened in favour of a direct representation of time, Alumbramiento is an exception : here the narrative, acting like a veritable explosion engine, by virtue of its force relegates time to its classic status as a measure of movement. While the attachment to a certain cinema of contemplation is always present in the shots that can be described as descriptive, the main thrust of Alumbramiento is an arrow that unstoppably spans the distance between the beginning of the film and its end. Paradoxically, Erice's most narrative film, the one that relies most heavily on the linear and irreversible nature of time, is at the same time the one in which the poetics of circularity, present in the filmmaker's work since his first feature-length film, takes up the most space and achieves its most accomplished expression. Organically integrated into the progression of the action, all the circularities scattered throughout Alumbramiento, starting with that of its structure, are an involutive force that can only unfold within a time that is necessarily progressive. This article sets out to analyse the way in which this tension is constructed, as well as its repercussions on the demarcation - perhaps too simplistic - between linear and circular time, both in terms of film and reality.